Hepatitis C treatment outcomes for Australian First Nations Peoples: equivalent SVR rate but higher rates of loss to follow-up - Clark, Paul J.; Valery, Patricia C.; Ward, James; Strasser, Simone I.; Weltman, Martin; Thompson, Alexander; Levy, Miriam T.; Leggett, Barbara; Zekry, Amany; Rong, Julian; Angus, Peter; George, Jacob; et al. (BMC gastroenterology, 2022)
Background First Nations Peoples of Australia are disproportionally affected by hepatitis C (HCV) infection. Through a prospective study we evaluated the outcome of direct-acting antiviral (DAA) therapy among First Nations Peoples with HCV infection. Methods Adults who initiated DAA therapy at one of 26 hospitals across Australia, 2016-2019 were included in the study. Clinical data were obtained from medical records and the Pharmaceutical and Medicare Benefits Schemes. Outcomes included sustained virologic response (SVR) and loss to follow-up (LTFU). A multivariable analysis assessed factors associated with LTFU. Results Compared to non-Indigenous Australians (n = 3206), First Nations Peoples (n = 89) were younger (p < 0.001), morel likely to reside in most disadvantaged (p = 0.002) and in regional/remote areas (p < 0.001), and had similar liver disease severity. Medicines for mental health conditions were most commonly dispensed among First Nations Peoples (55.2% vs. 42.8%; p = 0.022). Of 2910 patients with follow-up data, both groups had high SVR rates (95.3% of First Nations Peoples vs. 93.2% of non-Indigenous patients; p = 0.51) and 'good' adherence (90.0% vs. 86.9%, respectively; p = 0.43). However, 28.1% of First Nations Peoples were LTFU vs. 11.2% of non-Indigenous patients (p < 0.001). Among First Nations Peoples, younger age (adj-OR = 0.93, 95% CI 0.87-0.99) and treatment initiation in 2018-2019 vs. 2016 (adj-OR = 5.14, 95% CI 1.23-21.36) predicted LTFU, while higher fibrosis score was associated with better engagement in HCV care (adj-OR = 0.71, 95% CI 0.50-0.99). Conclusions Our data showed that First Nations Peoples have an equivalent HCV cure rate, but higher rates of LTFU. Better strategies to increase engagement of First Nations Peoples with HCV care are needed. Keywords: Sustained viral response, Liver fibrosis, Data linkage, Loss to follow-up